2021
DOI: 10.1371/journal.pone.0259221
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin and isoniazid drug resistance among patients diagnosed with pulmonary tuberculosis in southwestern Uganda

Abstract: Multidrug-resistant tuberculosis (MDR-TB) has become a major threat to the control of tuberculosis globally. Uganda is among the countries with a relatively high prevalence of tuberculosis despite significant control efforts. In this study, the drug resistance of Mycobacterium tuberculosis to rifampicin (RIF) and isoniazid (INH) was investigated among patients diagnosed with pulmonary tuberculosis in Southwestern Uganda. A total of 283 sputum samples (266 from newly diagnosed and 17 from previously treated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The low proportions of INH mono-resistance at 9.8% (4.8–17.3) in this study may be attributed to a selection bias as a result of our selected study population. However, the higher proportions of RIF mono-resistance at 90.2% (82.7–95.2) are in agreement with two studies that raise awareness of increasing levels of this type of drug resistance among TB patients [ 24 , 25 ]. Malenfant and Brewer [ 24 ] recently reported that the availability of diagnostic assays that allow for quick detection of RIF resistance has increased awareness of patients with rifampicin mono-resistant TB (RR-TB), which was previously thought to be uncommon [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The low proportions of INH mono-resistance at 9.8% (4.8–17.3) in this study may be attributed to a selection bias as a result of our selected study population. However, the higher proportions of RIF mono-resistance at 90.2% (82.7–95.2) are in agreement with two studies that raise awareness of increasing levels of this type of drug resistance among TB patients [ 24 , 25 ]. Malenfant and Brewer [ 24 ] recently reported that the availability of diagnostic assays that allow for quick detection of RIF resistance has increased awareness of patients with rifampicin mono-resistant TB (RR-TB), which was previously thought to be uncommon [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…Mono-resistance to RIF was higher than INH monoresistance and is backed by recent studies that have raised more awareness on this phenomenon [ 24 , 25 ]. The low proportions of INH mono-resistance at 9.8% (4.8–17.3) in this study may be attributed to a selection bias as a result of our selected study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who do not get adequate treatment may develop drug-resistant MTB (acquired resistance), which may then transmit to others (primary resistance) (Micheni et al 2021). Multidrugresistant tuberculosis (MDR-TB), which is defined as resistance to both isoniazid (INH) and rifampin (RIF for treating TB), is extremely concerning since second-line antimycobacterial medications need to be used over an extended period of time, are costly, and have a number of adverse effects (Zetola et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“… 4 In other countries, such as Uganda, the rate of rifampicin resistance was 10.2% in newly treated patients and 23.5% in re-treated patients in 2018–2019. 7 In Ethiopia, the laboratory-detected rifampicin resistance rate was 6.3%. 8 As a representative province in eastern China, Zhejiang Province also has its own unique TB drug resistance rate.…”
Section: Introductionmentioning
confidence: 99%